Glucagon-like peptide-1 receptor agonists rescued diabetic vascular endothelial damage through suppression of aberrant STING signaling - Xuemin He; Siying Wen; Xixiang Tang; Zheyao Wen; Rui Zhang; Shasha Li; Rong Gao; Jin Wang; Yanhua Zhu; Dong Fang; Ting Li; Ruiping Peng; et al. (Elsevier, 2024)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) protect against diabetic cardiovascular diseases and nephropathy. However, their activity in diabetic retinopathy (DR) remains unclear. Our retrospective cohort study involving 1626 T2DM patients revealed superior efficacy of GLP-1 RAs in controlling DR compared to other glucose-lowering medications, suggesting their advantage in DR treatment. By single-cell RNA-sequencing analysis and immunostaining, we observed a high expression of GLP-1R in retinal endothelial cells, which was down-regulated under diabetic conditions. Treatment of GLP-1 RAs significantly restored the receptor expression, resulting in an improvement in retinal degeneration, vascular tortuosity, avascular vessels, and vascular integrity in diabetic mice. GO and GSEA analyses further implicated enhanced mitochondrial gene translation and mitochondrial functions by GLP-1 RAs. Additionally, the treatment attenuated STING signaling activation in retinal endothelial cells, which is typically activated by leaked mitochondrial DNA. Expression of STING mRNA was positively correlated to the levels of angiogenic and inflammatory factors in the endothelial cells of human fibrovascular membranes. Further investigation revealed that the cAMP-responsive element binding protein played a role in the GLP-1R signaling pathway on suppression of STING signaling. This study demonstrates a novel role of GLP-1 RAs in the protection of diabetic retinal vasculature by inhibiting STING-elicited inflammatory signals.